Myelodysplastic syndrome-like response after voriconazole treatment of systemic lupus erythematosus complicated with fungal infection: a case report - Xie, Guang-Liang; Wang, Xiao-Su; Hu, Ling-Yan; Wang, Yi; Gu, Xiangchen; Xu, Yan-Qiu (Frontiers in Medicine, 2023)
Background Voriconazole is mainly used to treat progressive and potentially life-threatening infections in immunocompromised patients. The adverse drug reactions related to voriconazole are varied. In some rare cases, the use of voriconazole can result in myelodysplastic syndrome (MDS)-like adverse reactions. Case presentation Here, we present a rare case of systemic lupus erythematosus patient with a fungal infection that developed MDS-like adverse reactions after treatment with voriconazole. The patient was admitted to the hospital because of 3 days of chest tightness and dyspnea. After the admission, the patient’s sputum culture showed Candida albicans infection, and voriconazole was prescribed to be taken orally. After using voriconazole, drug-related adverse reactions such as visual impairment, nausea, vomiting, hiccup, middle and lower abdominal pain, disorders of consciousness, delirium, hallucination, slow response, and subcutaneous ecchymosis appeared, as well as the gradually increased serum creatinine, oliguria, and aggravated lower limb edema. In addition, there was a decrease in peripheral blood cells, and MDS-like changes in bone marrow were indicated by bone marrow biopsy. After discontinuing voriconazole, drug-related adverse symptoms disappeared, and hematocytopenia and the changes in MDS were significantly improved, which was confirmed by a subsequent bone marrow puncture at a 6 months interval. Conclusion This case reminded us that when using voriconazole for treatment, individual differences in patients should be considered, and the blood concentration of voriconazole should be closely monitored. Otherwise, potential drugs that affect voriconazole metabolism should be noted, and related adverse symptoms of patients should be closely observed during medication to reduce the occurrence of adverse drug events.